The antiterrorist component of the law of armed conflicts - Антипенко, Анна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
Reveals the need for assessing terrorist conflicts within the international law of armed conflict, international humanitarian law and the recognition of their social identity. In assessment of terrorism as a form of armed conflict is trying to find the potential of international law of armed conflict to regulate combat this international crime